PENERAPAN SISTEM INFORMASI MANAJEMEN INVENTORY PADA CV MADJU DJAJA BANJARMASIN - sylvia, rika; Handriano, Rory; Maharani, Ni Made Sri (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, The purpose of this research is to determine the application of the inventory management information system at the CV Madju Djaja Banjarmasin company. The type of research used is descriptive qualitative. The data sources in this research are interviews. Data analysis uses Web-based programming, namely PHP Version 5.1.1 and MySQL database Version 5.0.18. The results of research using an inventory management information system, it can make it easier for company employees to process goods data such as inputting incoming and outgoing goods via computer and by using this system it can make it easier for the warehouse stock section to make monthly stock reports. Control and supervision of inventory can be carried out directly by the director because the information system can be accessed on the internet by entering a username and password which are only known by the company director and the warehouse stock section. So that there is no interference from other unrelated parties and can minimize the risks that occur.